PENGARUH TERPAAN INFORMASI COVID-19 PADA KONFERENSI PERS GUGUS TUGAS PERCEPATAN PENANGANAN COVID-19 DI TELEVISI TERHADAP KECEMASAN MASYARAKAT : Survei pada Masyarakat Jakarta Selatan - Jasmine Arundhati Karilasalma (2020)
This study discusses the effect of Covid-19 information exposure at a press conference task force acceleration of handling Covid-19 on the anxiety of the people of south Jakarta. Since the end of 2019, a viral pandemic disaster has occurred, known as the Corona Virus (Covid-19). Every day a press conference is held on several television stations as "Breaking News" about the development of information and the socialization of Covid-19 in Indonesia. The results of the study through the correlation test are the variable x (Covid-19 Information Exposure) to the variable y (anxiety) showing that there is a low correlation of 0.274. The results of the determination coefficient test are known to be 3.9%. The result of the hypothesis test with t count of 2 is greater than t table, so that Ho is rejected and Ha is accepted, which means that the greater influence of Covid-19 information exposure at the press conference task force for handling Covid-19 on television, the greater anxiety of the people of South Jakarta . Suggestions related to this research are that it can be developed further for next research that is testing the relationship with other variables, in addition it can be done in-depth interviews to enrich the results of the study and because the results of the study state that there is an influence although the magnitude tends to be small but for people who are susceptible to anxiety during this pandemic can reduce watching those shows.